Velocity Structure and Molecular Formation in the Polaris Molecular Cloud - Tomomi Shimoikura; Kazuhito Dobashi; Fumitaka Nakamura; Kotomi Taniguchi (The Astrophysical Journal)
We present a wide-field $(60^{′} × 30^{′} )$ study of a dense region within the Polaris Flare using ^12 CO, ^13 CO, and C ^18 O ( J = 1–0) observations at 15″ resolution, obtained with the Nobeyama 45 m Radio Telescope. The analysis reveals molecular gas formation occurring at column densities up to ∼10 ^21 cm ^−2 , evidenced by an anticorrelation between H i and CO distributions, indicating active atomic-to-molecular gas conversion. We found a threshold column density for molecular formation at ∼5 × 10 ^20 cm ^−2 , which is common among more evolved molecular clouds. The CO-to-H _2 conversion factor, X _CO , was found to be 0.7 × 10 ^20 H _2 cm ^−2 (K km s ^−1 ) ^−1 , lower than the solar neighborhood average. Our chemical models estimate the cloud’s age to be ∼​​​​​​10 ^5 –10 ^6 yr, suggesting an early stage of molecular cloud evolution. This interpretation is consistent with the observed low X _CO factor. While virial analysis suggests that the entire cloud is gravitationally unbound, we identified several filamentary structures extending from the main cloud body. These filaments show systematic velocity gradients of 0.5–1.5 km s ^−1 pc ^−1 , and analysis of the velocities shows that the molecular gas within them is falling toward the main cloud body, following a freefall model. This suggests ongoing mass accumulation processes through the filaments, demonstrating that gravitational processes can be important even at column densities of ∼10 ^21 cm ^−2 .